ON THE EXCITATION OF LOCAL ELECTRIC CURRENT IN THE BIOLOGICAL ENVIRONMENT - Igor Bondarenko; Oleg Avrunin (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the study in the article is to study the method of excitation of human body tissues using an electric current. The purpose of the work is to develop a method for exciting local current in a human body affecting the microcirculation of blood and excitability of local areas of muscle tissue during the treatment process. The article solves the following tasks: the creation of a model pattern of fabric, the rationale for the generation of electric current inside the sample, the development of the design of the current generation system and measuring the electrical response of the model sample of the tissue on the occurrence of electric current, determining the size and spatial current distribution in the model sample of the fabric, comparison The obtained current values with known and admissible in medical practice its values, determination of the advantages of the proposed method of excitation of current compared to the traditional used in medicine. The following methods were used: analysis of scientific publications for the subject of the study, the calculation of the expected current parameters in the model sample, the method of designing the nodes of the current generation and measurement system of the electrical response, the experimental method of excitation of the current and measuring the sample response to it. The following results were obtained: a new acoustic-magnetic method of exciting electric current in local areas of muscle tissue is justified, which allows determining for them the optimal values of the therapeutic current and the value of its threshold value. model samples of muscle tissue are created, a magnetohydrodynamic method of generating electric current inside the patient's body is justified, design of a system for generating current and measuring the electrical response of a model fabric sample to the occurrence of electric current in it; determining the magnitude and spatial distribution of the current in the model fabric sample; comparison of obtained current values with known and permissible values in medical practice and proved their safety for a person. Calculated ratios are obtained, which connect value of excited local current with parameters of ultrasonic radiation, external permanent magnetic field and biological medium. The materials have been found that the current density excited in the local area of the biological medium is independent of the ultrasound frequency and is determined mainly by the intensity of the ultrasound and the constant magnetic field. The advantages of the current excitation method according to the present invention over the conventional galvanic method of passing current through the patient's skin are the ability to generate current in any desired local area of the patient's tissue and its complete safety. Conclusions: The scientific foundations of the new method of excitation of local current inside the human body have been developed and experimentally tested on model samples. Using this method can significantly increase the effectiveness of the treatment process based on the effect of current on blood microcirculation in predetermined areas of muscle tissue and for the first time will allow distinguishing and determining with high accuracy thresholds of their excitability by electric current.